Reactive Lymphoid Hyperplasia of the Liver Incidentally Found in a 55-Year-Old Woman with a History of Ulcerative Colitis - Noritoshi Mizuta; Takuya Kikuchi; Shunsuke Kusano; Nobuya Sano (Case Reports in Surgery)
Reactive lymphoid hyperplasia (RLH) is a benign disease, rarely occurring in the liver. Reactive immune phenomenon has been reported in association with its occurrence, but the true pathogenesis is unknown. No case was reported in association with inflammatory bowel disease. We report a case of RLH of the liver in a patient with ulcerative colitis (UC). A 55-year-old woman with UC went to the outpatient clinic with abdominal pain, and antibiotics were prescribed with diagnosis of acute appendicitis. Imaging study detected a mass in the liver but ruled out appendicitis. She was referred to our hospital for further examination after pain improving. A 12 mm hypoechoic mass was detected in the liver on ultrasonography. There were no typical malignant findings on computed tomography and magnetic resonance imaging. Regular image follow-up was recommended, but the patient strongly requested surgery because of family history of malignant disease. Laparoscopic partial hepatectomy was performed. Histopathological findings revealed a conglomerate hyperplasia of lymphoid follicles with germinal centers. Infiltrating lymphocytes were non-neoplastic. Final diagnosis was RLH of the liver. UC is chronic inflammatory bowel disease and may be related to RLH, but there is no clear explanation at this point. This is the first known reported case of RLH of the liver in a patient with UC. But the relationship between the RLH and UC remains uncertain. Further investigation and case accumulation are necessary.